2015
DOI: 10.1016/j.lungcan.2015.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Responses to the multitargeted MET/ALK/ROS1 inhibitor crizotinib and co-occurring mutations in lung adenocarcinomas with MET amplification or MET exon 14 skipping mutation

Abstract: Introduction Genomic aberrations involving ALK, ROS1 and MET can be driver oncogenes in lung adenocarcinomas. Identification of tyrosine kinase inhibitors (TKIs) with activity against these tumors and of preclinical systems to model response are warranted. Methods We analyzed cases with lung adenocarcinomas for representative genomic aberrations, evaluated the response to the multitargeted MET/ALK/ROS1 crizotinib TKI in cases with MET aberrations and profiled lung cancer cell lines with the aforementioned ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 25 publications
2
44
0
1
Order By: Relevance
“…In another recent study, lung adenocarcinoma cell lines with ALK rearrangement, ROS1 rearrangement or MET amplification showed in vitro response to crizotinib and ceritinib (an ALK/ROS1 inhibitor) (30). The evaluation of a cohort of patients affected by lung adenocarcinoma performed in the same analysis revealed that putative genomic aberrations potentially targetable by crizotinib (ALK and ROS1 rearrangements, high level MET amplification or MET exon 14 skipping mutations) are present in the 10% of cases.…”
Section: Lung Cancermentioning
confidence: 96%
See 1 more Smart Citation
“…In another recent study, lung adenocarcinoma cell lines with ALK rearrangement, ROS1 rearrangement or MET amplification showed in vitro response to crizotinib and ceritinib (an ALK/ROS1 inhibitor) (30). The evaluation of a cohort of patients affected by lung adenocarcinoma performed in the same analysis revealed that putative genomic aberrations potentially targetable by crizotinib (ALK and ROS1 rearrangements, high level MET amplification or MET exon 14 skipping mutations) are present in the 10% of cases.…”
Section: Lung Cancermentioning
confidence: 96%
“…The evaluation of a cohort of patients affected by lung adenocarcinoma performed in the same analysis revealed that putative genomic aberrations potentially targetable by crizotinib (ALK and ROS1 rearrangements, high level MET amplification or MET exon 14 skipping mutations) are present in the 10% of cases. MET exon 14 skipping mutation was reported to predict response to anti-Met tyrosine kinase inhibitor (TKI) in lung adenocarcinomas (30).…”
Section: Lung Cancermentioning
confidence: 99%
“…The incidence of MET mutations in lung cancers is 3% in squamous cell lung cancers, 5.6% in NSCLC, and 8% in lung adenocarcinomas (29)(30)(31). The implications of MET JM domain mutations and receptor regulation on the clinical outcome of lung cancer patients have become evident in recent years (32)(33)(34)(35)(36)(37). Moreover, the importance of these Sema and JM domain mutations is not limited to lung cancer.…”
Section: Met Juxtamembrane and Sema Domain Mutationsmentioning
confidence: 99%
“…Most METex14 del mutations have been identified in lung adenocarcinoma, adenosquamous, or pulmonary sarcomatoid carcinoma subtypes, collectively comprise approximately 3% of non-small cell lung cancer (NSCLC), and are statistically exclusive with other known oncogenic drivers (4,8,9). Genetic, pharmacologic, and clinical studies have further established that this collection of mutations exhibit the characteristics of driver oncogenes and that MET inhibitors are clinically active in NSCLC patients with these mutations (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%